2022
DOI: 10.1097/dss.0000000000003670
|View full text |Cite
|
Sign up to set email alerts
|

Microneedling in Combination With 15% Trichloroacetic Acid Peel Versus 25% Pyruvic Acid Peel in the Treatment of Acne Scars

Abstract: BACKGROUNDAcne scars are a permanent disfiguring sequel of acne.OBJECTIVETo compare the efficacy of microneedling with 15% trichloroacetic acid (TCA) peel versus microneedling with 25% pyruvic acid peel in the management of postacne scars.MATERIAL AND METHODSThirty patients with atrophic acne scars were randomized into 2 groups receiving microneedling on both sides of the face at 0,6, and 12 weeks and 15% TCA on one side and 25% pyruvic acid on other side at 3,9, and 15 weeks. Acne scar scoring performed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Approximately 40% of acne sufferers develop clinically relevant scars and in darker skinned populations half or more develop pigmentary problems; 9,10 as with active lesions, these sequelae have an impact on life quality 3,4 . Further, they are often difficult to manage adequately 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 40% of acne sufferers develop clinically relevant scars and in darker skinned populations half or more develop pigmentary problems; 9,10 as with active lesions, these sequelae have an impact on life quality 3,4 . Further, they are often difficult to manage adequately 11 …”
Section: Introductionmentioning
confidence: 99%
“…3,4 Further, they are often difficult to manage adequately. 11 A variety of efficacious topical and systemic medical therapies for acne have been approved by regulatory bodies; however, their use can be limited by high costs, cutaneous irritation, possible teratogenicity, accessibility and efficacy-especially when patients are not able or are unwilling to use the medication for a suitable duration. Large-scale population-based studies have shown that overall medication adherence is low in acne.…”
mentioning
confidence: 99%